The Impact of Production and Price Risks on The Economic Behavior of Coconut Farmers' Households in Seruyan Regency, Central Borneo Province - Rusdi; Harianto; Sri Hartoyo; Tanti Novianti (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Production risk and price risk are problems that are often faced by coconut farmers. This is illustrated by the price and production instability faced by farmers, which will then have an impact on income and decision making in production and work allocation. The purpose of this study was to analyze the effect of changes in the level of production risk and price on the behavior of farmer households in coconut farming production decisions. This research was conducted in Seruyan Regency, Central Kalimantan Province with a total of 200 farmers as respondents. The production function and the risk function were analyzed using the Ordinary Least Square (OLS) method, while the farmer household economic model which was built using the simultaneous equation would be analyzed using the Two Stage Least Squares (2SLS) method. The results of the risk function analysis show that the risk of coconut production is directly proportional to the use of salt and herbicides. Land area, use of salt, herbicides and labor have a significant and positive effect on coconut production. The simulation results show an increased risk of negative impacts on the economy of coconut farmers' households. Keywords: production risk, price risk, household economy, coconut farmers